On the Evolution of Size and Productivity in Transition: Evidence from Slovenian Manufacturing Firms - Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2004)
This paper compiles a set of stylized facts on the evolution of firm size and labor and total factor productivity distributions during the process of transition. These facts are based on the data for all Slovenian manufacturing firms active between 1994 and 2003. Stylized picture of transition can be summarized as follows. Initially, we can distinguish between two types of firms: small and on average more productive and large and on average less productive firms. Removal of institutional restrictions has spurred growth of small firms and entry of new firms on one hand and decline and exit of large firms on the other. These simultaneous shifts have transfirmed the shape of firm size distribution from bimodal into unimodal. While labor and total factor productivity distributions exhibit large right-hand shifts and lower heterogeneity over time, firm productivity rankings changed substantially. Smaller firms, which were initially more productive, exhibited lower productivity growth rates and thus gradually lost their advantage. Commonly held view of transition as a process of reallocation of resources from inefficient state to efficient private firms is at odds with our results of aggregate labor and total factor productivity decompositions. Almost half of aggregate labor productivity growth can be explained by within firm growth and the rest by reallocation. Our evidence suggests that within firm growth seems to be related to the process of technological catching up of less productivelarge firms. These stylized facts may give a wrong impression of transition being a detfirministic process, while it is not. The process is stochastic and thus similar to those found for established market economies. Hence theoretical models of transition should reflect detfirministic features that we outlined and preserve stochastic elements introduced in now standard models of industrial dynamics.
Keywords: L11; L16; L60; 330; manufacturing; size; labor productivity; total factor productivity; catching up; distributions; transition; Unternehmenserfolg; Betriebsgröße; Produktivität; Verarbeitendes Gewerbe; Schätzung; Slowenien